A novel dietary inflammatory index reflecting for inflammatory ageing: Technical note. (November 2019) - Kanauchi, Masao; Shibata, Mitsuru; Iwamura, Masaki
Abstract: Objective: Chronic inflammation plays an important role in the development of several chronic diseases. Existing dietary inflammatory indexes require complicated calculations, which are difficult to use in clinical practice. We developed a new and simple index, based solely on the frequency of consumption of only 16 foods, to capture the inflammatory potential of diet. Methods: The new index, an empirical dietary inflammatory index (eDII), is based on 8 pro-inflammatory and 8 anti-inflammatory components. First, in a validation study, 168 community-dwelling persons were invited to participate and an inflammatory aging disease (IAD) score of each participant was calculated by total number of IADs. Second, in the nutritional epidemiologic study, we calculated the eDII for 1464 participants and compared the eDII with healthy diet quality scores. Results: In a validation study, when subjects were classified by eDII tertile, a higher eDII was significantly associated with a higher IAD score. In the nutritional epidemiologic study, a higher eDII was inversely associated with the Mediterranean diet score, the World Health Organization's healthy diet indicator, and the American Heart Association's recommended healthy diet score. Conclusions: The eDII is an easy and valid instrument to assess the inflammatory potential of dietary factors. This index is easy to use and does not require detailed estimations of nutrient intake. Highlights: We developed a new and simple index to capture the inflammatory potential of diet. The new index is based on 8 pro-inflammatory and 8 anti-inflammatory components. This index is related to an inflammatory aging disease score. This index is easy to use and does not require detailed estimations of nutrient intake.